Blue tits do not return faster to the nest in response to either short- or long-term begging playbacks. (January 2017) - Santema, Peter; Schlicht, Emmi; Schlicht, Lotte; Kempenaers, Bart
Abstract : In species with parental care, offspring often solicit food through elaborate begging displays. Begging is thought to be a reflection of offspring need, but short-term fluctuations in begging do not necessarily provide reliable information. Parents thus have to adjust their provisioning behaviour to the changing demands of their offspring, while minimizing the costs of responding to unreliable information. We conducted two experiments with blue tits, Cyanistes caeruleus, in which we tested how parents respond to short-term and long-term changes in begging intensity. In the first experiment we investigated how parents respond to increased begging during a single nest visit. In the second experiment we investigated how parents respond to increased begging during every nest visit for 1 h. Parents did not return faster to the nest during the short-term manipulation. Contrary to our expectations, however, parents also did not return faster to the nest in response to long-term manipulation. Instead, parents spent more time in the nestbox during both the short-term and the long-term manipulation. Our results highlight that the general pattern of a positive parental response to increased begging may not be a universal one. Comparisons across species and populations may help reveal the factors underlying variation in parental responsiveness to begging. Highlights: Parental responsiveness to offspring begging may depend on duration of begging. We tested how blue tit parents respond to short- and long-term changes in begging. They did not return faster when begging calls were played during a single nest visit. Nor did they return faster when calls were played during every nest visit for 1 h. A positive response to increased begging may not be as universal as often assumed.